MAPPING OF pH AND TEMPERATURE SOIL IN THE MALIKUSSALEH SITE CULTURAL RESERVE AREA - Agus Muliaman; Syafrizal Syafrizal; Arlin Maya Sari; Ucia Mahya Dewi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2023)
Cultural sites are important historical relics. Damage to cultural sites or artifacts is triggered by various factors. High levels of salinity in the soil or environment of cultural sites can be one of the triggers. Another factor can be soil pH which is related to the level of acidity and salinity of the soil. For this reason, it is important to monitor soil quality in cultural site areas to anticipate damage to cultural sites. This research aims to measure soil pH in the Malikussaleh cultural heritage site area and map soil quality conditions (pH and temperature) in the Malikussaleh cultural heritage area. The research location is in the Malikussaleh cultural heritage area in Samudera subdistrict. This research is a type of basic research with a quantitative approach. In this study, pH and temperature of soil were measured using pH meter and thermometer, respectively. The pH and soil temperature data obtained were interpreted based on correlation with regional conditions. Based on the measurement results, the soil in the Malikussaleh site area has an acidity level in the range of weak base and high acid (pH 4.5-7).